Respon Pemerintah Indonesia Terhadap Hak Asasi Anak dalam Konvensi Internasional (Refleksi Ius Constitutum dan Prospek Ius Constituendum) - Ngah, Anisah Che; Rahman, Abdul (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2014)
Children’s rights are well-established through various international conventions. But, the international conventions do not well implemented in Indonesian law. Besides that, international convention is often interpreted differently in Indonesian law. To guarantee children’s rights, the government and society of Indonesia must be effort to implement international conventions already ratified correctly.